A partial tyrannosauroid femur from the mid-Cretaceous Wayan Formation of eastern Idaho, USA. (November 2022) - Krumenacker, L. J.; Zanno, Lindsay E.; Sues, Hans-Dieter
Abstract: The diversity of mid-Cretaceous tyrannosauroids is poorly understood. We describe a partial tyrannosauroid femur from the Albian–Cenomanian Wayan Formation of eastern Idaho that helps to fill in an important spatiotemporal gap in the North American record of tyrannosaurs. This specimen, consisting of the proximal half of the bone, is morphologically similar to the femur of Moros intrepidus, a small-bodied tyrannosauroid from the Cenomanian Mussentuchit Member of the Cedar Mountain Formation of Utah, but not referable to this taxon. The Wayan femur lacks an autapomorphy diagnostic for Moros intrepidus, indicating the presence of a previously unrecognized tyrannosauroid taxon in the early Late Cretaceous of Laramidia. Histological results indicate that, at the time of death, this individual was at least five years old, skeletally immature, and undergoing growth at a moderate rate. The addition of this tyrannosauroid to the Wayan-Vaughn Assemblage provides additional evidence for the widespread distribution of various tyrannosauroid taxa in Laramidia during the early Late Cretaceous.